Hak Waris Anak Luar Kawin yang Diakui dalam Sistem Hukum Indonesia: Kajian Komparatif KUHPerdata BW dan KHI - Muhammad Akbar Rosyidi Datmi; Muhammad Yadi Harahap; Fauziah Lubis (TAQNIN: Jurnal Syariah dan Hukum, 2025)
The inheritance rights of acknowledged children born out of wedlock remain a contested issue in Indonesia due to the coexistence of two legal systems: the Indonesian Civil Code (Burgerlijk Wetboek/BW) and the Compilation of Islamic Law (KHI). These legal regimes differ significantly in regulating the civil status and inheritance rights of such children, creating legal uncertainty and normative inconsistency. This study employs normative legal research using statutory, historical, conceptual, comparative, and maqāṣid al-sharīʿah approaches. Primary legal sources include the Civil Code, the Compilation of Islamic Law, and Constitutional Court Decision No. 46/PUU-VIII/2010, supported by relevant legal doctrines and scholarly literature. The data were analyzed through qualitative legal interpretation using systematic, teleological, and comparative methods. The study finds that the Civil Code recognizes civil relations between an acknowledged child born out of wedlock and the acknowledging parent through the mechanism of erkenning, thereby granting limited inheritance rights. In contrast, the Compilation of Islamic Law recognizes lineage only through the mother and her family, excluding inheritance rights from the biological father. Constitutional Court Decision No. 46/PUU-VIII/2010 introduced a significant shift by recognizing civil relations between children born out of wedlock and their biological fathers based on scientific evidence. From a maqāṣid al-sharīʿah perspective, protecting such children involves not only the preservation of lineage (ḥifẓ al-nasl) but also the protection of human dignity and property rights (ḥifẓ al-nafs and ḥifẓ al-māl). The study proposes a model of limited inheritance rights with Islamic justification to harmonize legal certainty, lineage protection, and social justice within Indonesia’s plural legal system.